Multi-layered historicity of the present : approaches to social science history - Vauhkonen, Jussi; Rainio-Niemi, Johanna; Haggrén, Heidi (Politiikan ja talouden tutkimuksen laitoksen julkaisuja, ISSN 2243-3635, 2013)
"This book celebrates Professor Pauli Kettunen on his sixtieth birthday. In Pauli Kettunen's scholarship as well as in this collection, history meets social sciences in a manner that render distinctions between the two unnecessary. This book challenges simplistic views to history as 'a background' or 'development', opening up sophisticated perspectives to many up-to-date debates on, for instance, nationalism and globalization or the Nordic welfare models."--Takakansi.
Keywords: Kettunen, Pauli, : 1953-; Kettunen, Pauli, : 1953- : juhlajulkaisut; Palmgren, Raoul; historiantutkijat; historiantutkimus; sosiaalihistoria; taloushistoria; yhteiskuntatieteet; sosiaalitieteet; työväenluokka; sosiaalipolitiikka; hyvinvointipolitiikka; yritykset; sairausvakuutus; eläkeikä; toimeentuloturva; historia; juhlajulkaisut; nationalismi; historiker (forskare); historieforskning; socialhistoria; ekonomisk historia; samhällsvetenskaper; socialvetenskaper; arbetarklassen; socialpolitik; välfärdspolitik; företag; sjukförsäkring; pensionsålder; utkomstskydd; festskrifter; nationalism